Electronic and Photovoltaic Properties of p-Si/PCBM:MEH-PPV Organic-Inorganic Hybrid Photodiode - Yakuphanoğlu, Fahrettin; Farooq, W. A. (Polish Acad Sciences Inst Physics, 2011)
The photovoltaic and electronic properties of p-Si/poly[2-methoxy,5-(2-ethyl-hexyloxy)-1,4-phenylenevinylene] (MEH-PPV):[6, 6]-phenyl C-61-butyric acid methyl ester (PCBM) organic-inorganic device have been investigated. The current-voltage characteristic of p-Si/PCBM:MEH-PPV photodiode includes series resistance effect and the diode indicates a non-ideal behavior. The photovoltaic effect in p-Si/PCBM:MEH-PPV photodiode is based on the formation of excitons and subsequent dissociation and charge collection at the electrodes. It is evaluated that p-Si/PCBM:MEH-PPV device is a photodiode with V-oc of 84 mV and I-sc of 3.47 nA electronic parameters.
Keywords: Current-Voltage Characteristics; Si/Al Diode; Solar-Cells; Parameters; Temperature; History